Obrazovanje, istraživanje i održivo upravljanje šumskim resursima kao faktor održivog razvoja u Bosni i Hercegovini / Education, Research and Sustainable Forest Management as a Factor of Sustainable Development in Bosnia And Herzegovina - Avdibegović, Mersudin; Delić, Sabina; Bećirović, Dženan; Marić, Bruno; Brajić, Amila; Hukić, Emira; Bogunić, Faruk; Vojniković, Sead; Ballian, Dalibor; Halilović, Velid; Hajrudinović-Bogunić, Alma; Avdagić, Admir; et al. (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The sustainable forest management concept contains the essence of the sustainable development paradigm - meeting the current needs of society without compromising the needs of future generations. The strategic commitment of the Faculty of Forestry University of Sarajevo is aimed at quality education of forestry experts, conducting innovative research and the most intensive cooperation with the economy. The methodological approach in this paper is based on a critical analysis of the scope of the educational-research process at the Faculty of Forestry University of Sarajevo, and the potentials of sustainable forest management in BiH, to determine to what extent higher education and research on environmental, sociological and economic aspects of forest management can affect positive changes in BiH society. Apart from identifying the benefits of forest ecosystems in the context of contributing to sustainable development, the research on the attitudes of teaching staff related to the contribution of the educational-research process to general goals of sustainable development from the 2030 Agenda was conducted. The results of this paper show that the concept of sustainable forest management, as it is realized in educational-research process at the Faculty of Forestry University of Sarajevo, has significant potential to contribute to sustainable development in BiH. This contribution is reflected in biodiversity conservation, mitigation of climate change, carbon storage, prevention of natural disasters, impact on the stability of water and soil, energy supply from renewable sources, continuous economic growth, socially responsible production and consumption, job security, development of rural and urban areas as well as maintaining and improving the psychophysical health of the population. Based on the obtained results, it can be concluded that sustainable forest management, grounded on scientific postulates, understanding of diversity of forest ecosystem services and dynamics in society's requirements towards forests, multidisciplinary and cross-sectoral cooperation, can be an important factor of sustainable development in BiH.